The Effect of Using A Digital Nutrition Application on The Knowledge and Attitudes of Mothers With Children Aged 1–5 Years Regarding Undernutrition - Maulina Mawaddah; Eka Sylviana Siregar (Jurnal Ners, 2026)
Abstract Undernutrition among toddlers remains a public health issue in Indonesia. Mothers’ limited knowledge and attitudes toward child nutrition are key factors contributing to this problem. This study aimed to analyze the effect of a digital nutrition application on the knowledge and attitudes of mothers with children aged 1–5 years. A quantitative approach was used with a quasi-experimental design and a pretest-posttest control group. A total of 60 mothers participated, divided into an intervention group (using the digital nutrition app) and a control group (using printed leaflets). The results showed a significant increase in knowledge and attitude scores in the intervention group compared to the control (p < 0.05). Furthermore, most respondents perceived the digital nutrition application as more practical. In conclusion, the digital nutrition app had a positive effect on improving maternal knowledge and attitudes toward child undernutrition and was considered a practical tool for health education. Keywords: undernutrition, toddler mothers, digital application, knowledge, attitude